Sex differences in younger school age children’s body weight categories - Zbořilová, Vendula; Přidalová, Miroslava; Sigmundová, Dagmar (Anthropological Review, 2021)
The issue of inadequate or excessive children’s body weight, particularly in relation to their health, is also discussed by Czech experts in physical anthropology, auxology, paediatrics, endocrinology, etc. Overweight and obesity occur already at a younger school age, and some domestic and foreign sources report a higher prevalence in boys. The objective of this study was to describe distribution range in body weight categories among Czech children of younger school age (6 to 11 years) taking into account age and sex. Our research was carried out at 23 primary schools in 5 regions of the Czech Republic between 2014 and 2018. The research group consisted of 2,099 children aged 6 to 11 years (boys n = 1,015, 48.4%; girls n = 1,084, 51.6%). Probands were subjected to the standard anthropometric examination with body weight being assessed using the following assessment standards: the Czech national growth references, Nationwide Anthropological Survey of Czech Children and Adolescents (NAS), World Health Organisation (WHO) growth standards, and International Obesity Task Force (IOTF) references were used. Statistical tests were carried out at a significance level of p ≤ 0.05; residual analysis. According to all three assessment standards, the highest prevalence of children with normal body weight was in both sexes; 45.8% of girls and 48.4% of boys, using the Czech assessment reference. Overweight and obesity were more predominant in boys (7.9% and 8.7%) than in girls (7.7% and 7.5%). One point seven percent of boys and girls were equally underweight, whereas the percentage of girls (22.3%) with reduced body weight was higher than in boys (20.3%). A significant difference between boys and girls was found in the category of reduced body weight in nine-year-old children. Using internationally recommended BMI references, more children fell into the category of normal body weight. Significant differences, in accordance with IOTF, between the number of severely underweight boys and girls were observed in 7-year-olds, slightly underweight in 9- and 11-year-olds, and overweight in 7-year-olds. In accordance with the WHO growth standards, significant differences appeared between eight-year-olds and eleven-year-olds obese boys and girls. Our research study revealed the prevalence in younger school age children body weight categories. Different BMI references were used to classify body weight. Significant differences between the number of boys and girls were observed in certain weight categories in seven-year-old, eight-year-old, nine-year-old and eleven-year-old children. Thus, the study confirmed the presence of differences in the number of boys and girls in specific body weight categories.